Tinjauan Efektivitas Kegiatan Penagihan Pajak Pada KPP Pratama Pontianak Barat - Muhammad Fahmi; Rini Adriani Auliana (STIE Atma Bhakti, 2026)
The taxation system in Indonesia is a self-assessment system, a taxation system that states that taxpayers are given the trust and authority to calculate, pay, and report their own taxes, which means commitment and compliance come from the taxpayer. Although the applicable system guarantees willingness, tax collection is still necessary and plays an important role as a law enforcement mechanism. In addition to being part of the law enforcement function, tax collection is also expected to increase tax revenue from the disbursement of taxpayer arrears. This study aims to measure the effectiveness of tax collection activities on tax revenue through the disbursement of tax arrears at the West Pontianak Pratama Tax Service Office in 2024. The method used is a quantitative descriptive method. The observational data used is data on tax collection activities in 2024 at the West Pontianak Pratama Tax Service Office in the form of secondary data and related documents. Based on the results of the study, it can be stated that tax collection activities have been effective with a realization value of 93.44%. This research can be used as observation material to improve the effectiveness of tax collection implementation at the West Pontianak Pratama Tax Service Office.